Succession of endophytic fungi and rhizosphere soil fungi and their correlation with secondary metabolites in Fagopyrum dibotrys - Ma, Nan; Yin, Dengpan; Liu, Ying; Gao, Ziyong; Cao, Yu; Chen, Tongtong; Huang, Ziyi; Jia, Qiaojun; Wang, Dekai (Frontiers in Microbiology, 2023)
Golden buckwheat (Fagopyrum dibotrys, also known as F. acutatum)Fagopyrum dibotrys is a traditional edible herbal medicinal plant with a large number of secondary metabolites production and is considered to be sources of therapeutic compounds. Different ecological environments have a significant impact on their compound content and medicinal effects. However, little is known about the interactions between soil physicochemical properties and rhizosphere or endophytic fungal communities and secondary metabolites in F. dibotrys. In this study, the rhizosphere soil and endophytic fungal communities of F. dibotrys of five different ecological regions in China were identified based on high-throughput sequencing methods. The correlations between soil physicochemical properties, active components (total saponins, total flavonoids, proanthocyanidin, and epicatechin), endophytic and rhizosphere soil fungi of F. dibotrys were analyzed. The results showed that soil pH, soil N, OM, and P, were significantly correlated with the active components of F. dibotrys.